Desempenho Sustentável das Agroindústrias Familiares de Cascavel – PR - Rocha, Patrícia Maria Reckziegel da (2019)
The familiar agroindustry disagrees with traditional agribusiness since it assumes some familiar agriculture features of and has established itself as an example of applied reproduction by many farmers. It is a way that small farmers have found out to bring diversification into their production and increase their income and to remain in the countryside. The policies development must be stimulated since there is a great need to help agro-industries to be sustainable and consequently take care of their survival. The great discussion about sustainability is how to measure it so that it does not become a subjective concept. Thus, the general objective is to evaluate the sustainable performance of family agroindustries in Cascavel - PR considering the economic, social and environmental dimensions. Thus, the qualitative approach is applied to achieve this dissertation goal. This research consisted of two phases: in its first phase, a study was carried out to identify the categories of sustainability analysis that could be applied to familiar agribusiness; in its second phase, the categories of analysis was applied to familiar agribusiness of Cascavel-PR. The first phase of this research has an exploratory characteristic, and the second phase, the elements to be applied to the family agroindustries of Cascavel - PR were selected.. The studies concerned about familiar agribusiness groups and the surveyed actors are the managers of those familiar agribusiness groups, the Emater extensionist and the public prosecutor from SIM. The case study of this research used as data collection tool some interviews from a structured questionnaire. Additionally, documentary research and observation were used as well. With the general objective of proposing a set of applicable categories of sustainability analysis to Cascavel city context based on familiar agribusiness groups, this research considered as achieved those goals, constituting as an important tool to analyze the sustainability of rural enterprises. Despite all the efforts made by managers, as well as by the agencies that have provided some assistance, it can be considered that familiar agribusiness enterprises still need some adjustments to be fully sustainable regarding environmental, economic and social dimensions of sustainability